2017
DOI: 10.3390/environments4010021
|View full text |Cite
|
Sign up to set email alerts
|

Currently Commercially Available Chemical Sensors Employed for Detection of Volatile Organic Compounds in Outdoor and Indoor Air

Abstract: Abstract:The paper presents principle of operation and design of the most popular chemical sensors for measurement of volatile organic compounds (VOCs) in outdoor and indoor air. It describes the sensors for evaluation of explosion risk including pellistors and IR-absorption sensors as well as the sensors for detection of toxic compounds such as electrochemical (amperometric), photoionization and semiconductor with solid electrolyte ones. Commercially available sensors for detection of VOCs and their metrologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
167
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 83 publications
1
167
0
1
Order By: Relevance
“…This excitation (sensor response in the form of analytically useful signal) occurs in every sensor with different extent. Such excitation yields characteristic set of signals from particular sensors called a response vector of sensor matrix or electronic nose [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This excitation (sensor response in the form of analytically useful signal) occurs in every sensor with different extent. Such excitation yields characteristic set of signals from particular sensors called a response vector of sensor matrix or electronic nose [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of construction, they are equipped with a set of several chemical gas sensors. The commercially available volatile organic compounds sensors are the most commonly used sensor types [8,9]. E-noses in their functioning resemble the sense of human smell ( Figure 1).…”
Section: Electronic Nosementioning
confidence: 99%
“…Previous studies have shown that the theoretical dependence (2) is linear [8]. For this reason, a multiple linear regression model (3) was proposed combining the odour intensity with the electronic nose sensor signals:…”
Section: Electronic Nosementioning
confidence: 99%
“…The optical properties measured can be absorbance, reflectance, luminescence, light polarization, Raman and others. Optical sensors have found many applications in various fields, including biomedical, clinical, environmental monitoring and process controlling [12][13][14][15][16][17][18]. They are an attractive analytical tool, whenever continuous monitoring and real-time information is desired.…”
Section: Optical Sensorsmentioning
confidence: 99%